Peran Kantor Pertanahan dalam Penyelesaian Sengketa Tanah antara Masyarakat Desa Pakis dengan Perhutani Kabupaten Kendal - Saputro, Doni; Setiajid, Setiajid; Susanti, Martien Herna (Unnes Political Science Journal, 2017)
Land is included into one of human need which is functioning during the life and dead of the human himself. On one hand, the development of the era increases the needs of land. On the other hand, the land is unrenewable. It comes from the limitation of land-availability factors cannot afford the human breeding increase. Therefore, there is a big possibility of getting land-lawsuit among people and the officials. It can be seen from what happens in Pakis village with the Forestry department of Kendal. Both of them are claiming the right of land owmership so that it needs mediation for the problem solving. This study is aimed at knowing the influence of Landlordy-department as the mediator and knowing the obstacles of this case. This study uses qualitative study by doing interviews to the informants related to this land-lawsuit case. The writer found that Kendal have passed through two mediation session and no clear result so the Land Office conduct the caucus as an alternative dispute settlement land by the people Village Pakis with Perhutani Kendal. The main closure is that Forestry Department prosecutes the disputed-land in Pakis Village legally owned by the department and certified by the Forestry Department.